Joey Pigza loses control - Gantos, Jack (Farrar, Straus and Giroux, 2000)
Joey, who is still taking medication to keep him from getting too wired, goes to spend the summer with the hard-drinking father he has never known and tries to help the baseball team he coaches win the championship.